2021
DOI: 10.1002/fsn3.2225
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the structural properties and in vitro digestion of rice flours

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
3
8
0
Order By: Relevance
“…HCY had the highest GI compared to the other pigmented rice samples. Kabir et al (2021) stated that there is an inverse relationship between GI and amylose, which was supported by the current results as the amylose contents of the red rice (HHB), brown rice (HCY) and purple rice (RB) were 25%, 20.5% and 23.3% respectively (Ascheri et al, 2012;Thongkaew and Singthong, 2020;Farooq et al, 2021).…”
Section: Nutritional Propertiessupporting
confidence: 78%
See 1 more Smart Citation
“…HCY had the highest GI compared to the other pigmented rice samples. Kabir et al (2021) stated that there is an inverse relationship between GI and amylose, which was supported by the current results as the amylose contents of the red rice (HHB), brown rice (HCY) and purple rice (RB) were 25%, 20.5% and 23.3% respectively (Ascheri et al, 2012;Thongkaew and Singthong, 2020;Farooq et al, 2021).…”
Section: Nutritional Propertiessupporting
confidence: 78%
“…The popularity of rice is continuously increasing due to its nutritional, nutraceutical, gluten-free and hypoallergenic characteristics, which makes it particularly suitable for the preparation of ready-to-use products (Swaminathan and Guha, 2018). Red rice contains 10.5% protein, 3.5% dietary fiber and 25% amylose; brown rice contains 2.6% protein, 3.7% dietary fiber and 20.5% amylose; and purple rice contains 9.3% protein, 1.4% dietary fiber and 23.3% amylose (Ascheri et al, 2012;Settapramote et al, 2018;Veni, 2019;Thongkaew and Singthong, 2020;Farooq et al, 2021). Several studies have suggested that intake of pigmented rice has profound health benefits due to the presence of various antioxidants, such as polyphenols, flavonoids, anthocyanins, vitamin E, phytic acid and γoryzanol (Settapramote et al, 2018;Maulani et al, 2019;Veni, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Amylose is one of the key components that significantly influences the physicochemical properties and starch digestibility [1,16]. The amylose contents of pineapple stem, cassava, corn, and rice starches are presented in Table 1.…”
Section: Amylose Contentmentioning
confidence: 99%
“…Normally, root and tuber starches have lower amylose content than normal cereal starches. Starches with high amylose content help to delay starch digestion and lower blood glucose levels [16,18], which is useful for the production of low glycemic index foods.…”
Section: Amylose Contentmentioning
confidence: 99%
“…Drechsler & Bornhorst (2018) found the hardness of white rice and brown rice after 240 min of digestion in glass tubes was 1.0 ± 0.1 and 3.7 ± 0.3, respectively, which means that white rice was easier to digest than brown rice. Similarly, in the study of the pasted rice flour, the digestion rate and maltose release of white rice flour (0.048 and 55.7, respectively) were greater than those of black rice flour (0.040 and 49.6) and brown rice flour (0.036 and 46.1) (M. A. Farooq et al., 2021). The low rate of starch digestion in black rice can be explained by the presence of polyphenolic compounds and proteins, which may limit the gelatinization and thus the digestion of starch (Klunklin & Savage, 2018).…”
Section: Starch Digestibility Of Wgrmentioning
confidence: 90%